Impact of the foraging activity of Apis mellifera adansonii Latreille (Hymenoptera: Apidae) and Bradyrhizobium fertilizer on pollination and yield components of Glycine max L. (Fabaceae) in the field - Kengni, Stephanie Beaudelaine; Tchuenguem Fohouo, Fernand-Nestor; Ngakou, Albert (International Journal of Biological Research, 2015)
To determine the impact of Apis mellifera adansonii and Bradyrhizobium on pod and seed yields of Glycine max, field trials were carried out during 2012 and 2013 cropping seasons. Hence, 120 to 25658 flowers were labeled each year and divided into five treatments, differentiated according to whether plots were inoculated with Bradyrhizobium or not, or plants were protected from insects activities or not and the last treatment with flowers isolated then opened only to A. m. adansonii. The effects of Bradyrhizobium on nodulation, plant biomass and seed yield, as well as the foraging behavior of A. m. adansonii on flowers, the number of seeds per pod and the normal seeds' rate were evaluated. Results indicate that Bradyrhizobium significantly increased the number of flowers (P<0.001), root nodules (P<0.0001), plant biomass (P<0.0001), pod and seeds yields in inoculated plots. A. m. adansonii foraged on G. max flowers from 09.00 a.m. to 16.00 p.m. and throughout the whole blooming period. This insect intensely harvested only nectar. By comparing the yields of unprotected flowers to those of flowers isolated then opened to A. m. adansonii, 35.85% increase fructification index, and 73.09% increase in the number of seeds per pod due to this bee were recorded. The synergistic activity of insects and Bradyrhizobium increased the number of seeds per pod by 32.16% and the percentage of normal seeds by 32.87%. Our results reveal that inoculation of soybean plant at sowing with Bradyrhizobium and installation of hives close to the field could be recommended for a sustainable pods and seed yield improvement of this crop.